Hostile Attribution Bias Mediates the Relationship Between Structural Variations in the Left Middle Frontal Gyrus and Trait Angry Rumination - Wang, Yueyue; Zhu, Wenfeng; Xiao, Mingyue; Zhang, Qin; Zhao, Yufang; Zhang, Hao; Chen, Xu; Zheng, Yong; Xia, Ling-Xiang (Frontiers in Psychology, 2018)
Abstract: Angry rumination is a common mental phenomenon which may lead to negative social behaviors such as aggression. Although numerous neuroimaging studies have focused on brain area activation during angry rumination, to our knowledge no study has examined the neuroanatomical and cognitive mechanisms of this process. In this study, we conducted a voxel-based morphometry analysis, using a region of interest analysis to identify the structural and cognitive mechanisms underlying individual differences in trait angry rumination (as measured by the Angry Rumination Scale) in a sample of 82 undergraduate students. We found that angry rumination was positively correlated with grey matter density in the left middle frontal gyrus, which is implicated in inhibition control, working memory, and emotional regulation. The mediation analysis further revealed that hostile attribution bias (as measured by the Social Information Processing–Attribution Bias Questionnaire) acted as a cognitive mechanism underlying the positive association between the left middle frontal gyrus density and trait angry rumination. These findings suggest that hostile attribution bias may contribute to trait angry rumination, while the left middle frontal gyrus may play an important role in the development of hostile attribution bias and trait angry rumination. The study reveals the brain mechanisms of trait angry rumination and plays a role in revealing the cognitive mechanisms of the development of trait angry rumination.